Δ9‐Tetrahydrocannabinol‐induced anti‐inflammatory responses in adolescent mice switch to proinflammatory in adulthood. Issue 4 (17th April 2014) - Moretti, Sarah; Castelli, Mara; Franchi, Silvia; Raggi, Maria Augusta; Mercolini, Laura; Protti, Michele; Somaini, Lorenzo; Panerai, Alberto E.; Sacerdote, Paola
Abstract : Δ9‐Tetrahydrocannabinol exposure in adolescent mice induces anti‐inflammatory responses; modulation persists into adulthood with immunity switched toward a proinflammatory phenotype. Abstract : Marijuana abuse is prominent among adolescents. Although Δ 9 ‐THC, one of its main components, has been demonstrated to modulate immunity in adults, little is known about its impact during adolescence on the immune system and the long‐lasting effects in adulthood. We demonstrate that 10 days of Δ 9 ‐THC treatment induced a similar alteration of macrophage and splenocyte cytokines in adolescent and adult mice. Immediately at the end of chronic Δ 9 ‐THC, a decrease of proinflammatory cytokines IL‐ 1β and TNF‐α and an increase of anti‐inflammatory cytokine IL‐10 production by macrophages were present as protein and mRNA in adolescent and adult mice. In splenocytes, Δ 9 ‐THC modulated Th1/Th2 cytokines skewing toward Th2: IFN‐γ was reduced, and IL‐4 and IL‐10 increased. These effects were lost in adult animals, 47 days after the last administration. In contrast, in adult animals treated as adolescents, a perturbation of immune responses, although in an opposite direction, was present. In adults treated as adolescents, a proinflammatory macrophage phenotype was observed (IL‐1β and TNF‐α were elevated; IL‐10 decreased), and the production of Th cytokines was blunted. IgM titers were also reduced. Corticosterone concentrations indicate a long‐lasting dysregulation of HPA in adolescent mice. We measured blood concentrations of Δ 9 ‐THC and its metabolites, showing that Δ 9 ‐THC plasma levels in our mice are in the order of those achieved in human heavy smokers. Our data demonstrate that Δ 9 ‐THC in adolescent mice triggers immune dysfunctions that last long after the end of abuse, switching the murine immune system to proinflammatory status in adulthood.